Game theory and contemporary conflicts - Dukiewicz, Tomasz; Spustek, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article presents the application of game theory in the context of civil and military security. Game theory is used to study conflict situations involving more than one decision-maker. Special emphasis was given to the significant role of information in modern military operations. The article contains examples illustrating similarities between civil and military problems.
Keywords: teoria gier; gra taktyczna; przewaga informacyjna